Game As Major Introducing Media To OPT For College - Inggrit Swastini Dewi; Ridwan Sanjaya; Hendra Prasetya (SISFORMA, 2017)
Today's development requires people to have higher education and expertise in a particular field. Because of that, many universities or colleges are beginning to open new majors to suit the increasingly growing and diverse interests. However, the increasing number of majors could make it difficult for many high school students in determining the university or colleges and department they should take. A lack of understanding of their own personal interests and talents, as well as information about said universities or colleges and majors also add to the difficulty of choosing.Therefore, an interesting and simple media to help students to know their potential, provide information about the majors according to their interests, and help them determine the right path is needed.The concept of this major introducing game is based on sources such as interviews with interviewees and questionnaires. In the game, players can find out their interests, talents and appropriate majors, as well as courses and professions related to those majors. Aptitude test in this game is based on Holland’s Theory.